Biodiversity and ecosystem services: Complementary approach for catchment protection and land use in northeastern Poland - Marta Sokół; Grażyna Łaska (Ecological Indicators, 2024)
The concept of ecosystem services introduced a new view on the relationship between biodiversity and goods of human well-being. Are both ideas, biodiversity and ecosystem services, mutually beneficial for catchment protection? We aimed to explore how and to what extent specified the environmental and economic criteria determined the protection and urban land use intensity in the catchment in northeastern Poland. The relation between biodiversity, ecosystem services and land use intensity was made using 14 criteria that are also weights in the Analytic Hierarchy Process (AHP) and Borda multi-criteria decision analysis by using open public data resources, such as the Topographic Objects Database, digital terrain model, forms of nature protection, the database of recognised deposits of natural resources, geological map portals, Urban Spatial Information System and information on flood hazard areas, and open-source applications across the catchment.A combined procedure including categories of land cover elements, i.e. spatial objects of the surface, land use intensity and multi-criteria decision-making model, finally determined different variants for catchment biodiversity areas, from best (Variant 15) to worst (Variant 5) from 16 variants total. The spatial results showed that biodiversity and ecosystem services show an evident decline with increased land use intensity. Biodiversity was negatively correlated with the built-up areas and intensive land use in the central part of the catchment, but positively with which concerns the initial and final reaches of the river. The main factor affecting biodiversity was the distance of the river valley sections in the catchment area from the developed space of the city centre.Results suggest that biodiversity conservation in the catchment is needed for high biodiversity and low-intensity land use. For most green and agricultural areas with multifunctional benefits and, a good state is required compromise for ecosystem services and biodiversity. The functioning of the built-up areas and intensively used for humans is described only by the value of provisioning ecosystem services.